THE USE OF PORTFOLIO ASSESSMENT OF WRITING SKILL IN DESCRIPTIVE TEXT - Iman Abdul Halim; Agustin Hartati; Zubaedah Wiji Lestari (Universitas Galuh, 2019)
The objectives of the research are to find out the use of portfolio assessment of writing skill in descriptive text and the challenges faced by the teacher in the use of portfolio assessment of writing skill in descriptive text in SMP Negeri 1 Pagelaran Cianjur. The type of the research is qualitative research with case study method. In collecting the data, the researcher uses field notes, observation checklist, open-ended questionnaire, and documentation. The data were analyzed by reducing the non useful data, displaying the data, and drawing conclusion. The researcher uses data triangulation to get the validity of the data. Based on the research finding, the teacher implemented almost all the procedures of portfolio assessment proposed by Brown & Abeywickrama, the teacher designed the purpose of portfolio, the teacher designed the material of portfolio, the teacher designed the time of portfolio, the teacher designed the time for reviewing, the teacher designed the place for portfolio. The challenges faced by the teacher in the use of portfolio assessment of writing skill in descriptive text that the teacher has difficulties in giving feedback in a large class, less in controlling and guiding the students, and the teacher did not use the rubric for assessing the writing skill of the student’s task.